Statistical assessment of agricultural fertilizer impacts on water quality and environmental sustainability - Kien Vu Ngoc; Minh Duc Giang Trung (Heritage and Sustainable Development)
Agriculture is vital for global food production, but excessive fertilizer use poses serious risks to water quality and environmental health. Fertilizers, especially those high in nitrogen and phosphorus, can run off into nearby water bodies, causing nutrient pollution, algal blooms, and ecosystem damage. This study investigates how fertilizer use affects water quality by analyzing field data, including application rates and various water quality indicators. Water samples were collected from multiple sources over several months to account for seasonal changes and rainfall impacts. Key parameters measured included pH, dissolved oxygen, nitrate, phosphate, turbidity, organic matter, and trace metals like iron and zinc. Statistical tools—such as regression analysis, correlation studies, and multivariate techniques—were used to assess the relationship between fertilizer use and water quality. Results highlight the significant environmental impact of fertilizer runoff and emphasize the need for more sustainable management practices. These findings offer guidance for farmers, policymakers, and environmental advocates aiming to protect water resources while maintaining agricultural productivity.